Prácticas y creencias de hábitos de vida saludable y su relación con el rendimiento académico en estudiantes de contaduría - Ramírez Luna, Luna María (Universidad Antonio Nariño, 2021)
The objective of this study is to determine the practices and beliefs of healthy lifestyles and their relationship with academic performance in Public Accounting students. A descriptive cross-sectional study was carried out. The population universe is made up of all Public Accounting students at the Antonio Nariño University. The sample size consisted of 83 students to whom the Practices and Beliefs About Life Styles questionnaire was applied, validated by Arrivillaga, Salazar and Gómez, which assesses six dimensions of lifestyle: condition, physical activity and sport; Leisure time; self-care and medical care; Feeding Habits; consumption of alcohol, tobacco and other drugs; and I dream. The results of the research were statistically analyzed with the SPSS statistical package, using a univariate analysis with frequency and percentage tables for the qualitative variables and measures of central tendency and dispersion for the quantitative variables. The results showed favorable practices for health in most of the dimensions evaluated among the Public Accounting students surveyed, with the exception of two dimensions: physical activity and self-care and medical care. Paradoxically, with the results found in the practices on lifestyles, the university students hold correct beliefs about all the dimensions evaluated, especially regarding physical activity.